TolC is Required for Pathogenicity of Xylella fastidiosa in Vitis vinifera Grapevines - Joseph D. Reddy; Stephanie L. Reddy; Don L. Hopkins; Dean W. Gabriel (Molecular Plant-Microbe Interactions, 2007)
Xylella fastidiosa infects a wide range of hosts and causes serious diseases on some of them. The complete genomic sequences of both a citrus variegated chlorosis (CVC) and a Pierce's disease (PD) strain revealed two type I protein secretion plus two multidrug resistance efflux systems, and all evidently were dependent on a single tolC homolog. Marker exchange mutagenesis of the single tolC gene in PD strain Temecula resulted in a total loss of pathogenicity on grape. Importantly, the tolC¯ mutant strains were not recovered after inoculation into grape xylem, strongly indicating that multidrug efflux is critical to survival of this fastidious pathogen. Both survival and pathogenicity were restored by complementation using tolC cloned in shuttle vector pBBR1MCS-5, which was shown to replicate autonomously, without selection, for 60 days in Temecula growing in planta. These results also demonstrate the ability to complement mutations in X. fastidiosa.